THE ECOLOGY OF SPECIES, FAMILIES AND COMMUNITIES OF THE CONTEMPORARY BRITISH FLORA - Grime, J P (The New phytologist, 1984)
It is argued that detailed studies of the functioning of populations cannot by themselves lead to an understanding of British vegetation. Several complementary lines of investigation are required to explore the role of past and present interactions between habitat templet and plant characteristics. Strategy concepts provide a framework in which to assemble information from such diverse fields of ecological research, and recent results suggest that the present ecologies of populations, species, families and communities remain strongly conditioned by patterns of ecological specialization which predate the development of the post glacial flora